On the GCC Currency Union - Weshah Razzak (Economics and Econometrics Research Institute (EERI), 2009)
Essentially, the impact of the currency union on member countries depends on whether the common currency area is optimal in the sense that the effect of the asymmetric shocks is small, Mundell (1961). Typically, researchers use VAR of different types to analyze the data. For robustness, we use different methodologies. First, we use different estimators to estimate a small textbook model for the panel of the Gulf Cooperation Council countries (GCC) from 1970 to 2006, where the short-run equilibrium real output and the real exchange rate are determined by the intersection of the assets and goods markets equilibrium schedules. And the central bank fixes the exchange rate by keeping the money supply at a level where the domestic interest rate is equal to the foreign interest rate. Then we test for symmetry using the nonparametric Triples test, Randles et al. (1980). Third, we introduce a nonparametric multivariate statistic to test whether the variances of the shocks (the conditional variance) are equal across countries.
Keywords: F31; P28; C13; C33; 330; Optimum Currency Area; asymmetrical shocks and conditional variance